Genetic Algorithm based Stable Election Protocol for WSN - Kaur, Jasmeet; Sharma, Sukhwinder (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Network is an auspicious network in which wireless sensors are disseminated in a region for examining the physical world. Wireless sensor network consists of nodes called sensor nodes that does data acquisition and transmit the acquired data to sink. Since the power source has limited energy, so to prolong the lifetime of WSNs clustering is considered as an effective technique. One of the clustering techniques is Stable Election Protocol. The communication among nodes leads to loss of energy. Once, the energy of node is bygone then that node is declared as dead node and hence the network becomes shaky. The goal of SEP protocol is to improve the stability period of a network. So this paper focuses on increasing the stability period of WSN using Genetic Algorithm (GA). The GA is applied on SEP for the proficiency in stability period.